Procedura zmiany konstytucji RP na tle porównawczym: [The procedure for amending the Constitution of the Republic of Poland against a comparative background] (Studia Prawnicze / The Legal Studies, 2002)
Konstytucja zajmuje najwyższe miejsce w hierarchii źródeł prawa. Stabilność i trwałość porządku prawnego w państwie wynika z utrudnionego i obostrzonego pod wieloma względami trybu proceduralnego zmiany Konstytucji. Autorzy artykułu przedstawiają początki nowoczesnego konstytucjonalizmu na świecie, opisują obecnie obowiązujące konstytucje państw zachodnich jak i państw post-komunistycznych oraz szczegółowo przedstawiają procedurę zmiany konstytucji uregulowaną w Konstytucji z 1997 r. The Constitution occupies the highest place in the hierarchy of sources of law. The stability and permanence of the legal order of the state results from the procedural mode applicable to Constitution amendments, which is difficult and stringent in many respects. The authors of the article present the origins of modern constitutionalism across the world, describe the current constitutions of Western countries as well as of post-Communist countries and outline the details of the procedure for amending the constitution as regulated by the 1997 Constitution.